2004
DOI: 10.1111/j.1439-0442.2004.00642.x
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen Decreases Level of Immunoglobulins in Blood of the Hen (Gallus domesticus) without Alteration in Non‐Immunoglobular Fractions of Plasma Proteins

Abstract: The effect of tamoxifen (TMX), an anti-estrogen compound, on immunoglobulins (Ig) level in blood plasma of laying hens was investigated. TMX (4 mg/hen/day) was given per os for seven consecutive days; control hens received placebo. Blood samples were collected from the wing vein every day before TMX treatment, and plasma Ig levels were measured by means of Rlebodzinski's test. TMX significantly decreased plasma Ig levels, maximally by 51% on day 2 of the experiment. The observed reduction in Ig level was accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…In this study, treatment of broiler chicken with Tamoxifen in different doses caused a gradual decrease in follicle production rate and eventually led to an increase in the atretic follicles at different stages of atresia. This result is consistent with previous findings that have shown that treatment of laying hens with Tamoxifen leads to a reduction in the rate of egg laying and evokes a pause in egg laying [ 28 ]. The gradual decrease in the rate of egg laying after Tamoxifen administration is probably associated with the abolition of the central action of oestrogens at the hypothalamo-pituitary axis.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, treatment of broiler chicken with Tamoxifen in different doses caused a gradual decrease in follicle production rate and eventually led to an increase in the atretic follicles at different stages of atresia. This result is consistent with previous findings that have shown that treatment of laying hens with Tamoxifen leads to a reduction in the rate of egg laying and evokes a pause in egg laying [ 28 ]. The gradual decrease in the rate of egg laying after Tamoxifen administration is probably associated with the abolition of the central action of oestrogens at the hypothalamo-pituitary axis.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, treatment of laying hens with TAM caused a gradual decrease in egg-laying rate and eventually brought it to an end after twelve days of treatment. This result is consistent with previous findings which demonstrated that treatment of laying hens with TAM leads to a decrease in egg-laying rate and evokes a pause in egg laying (Wilson and Cunningham, 1981;Sechman et al, 2004a). The results obtained support the assumption that in the laying hen oestrogens are actively involved in the mechanism regulating the preovulatory release of LH.…”
Section: (A) (B)supporting
confidence: 83%
“…Therefore, it was applied in several previous studies in poultry to examine the role of oestrogens in physiological processes at various ages (Wilson and Cunningham, 1981;Asem and Hertelendy, 1986;Jaccoby et al, 1992;Lisowski and Bednarczyk, 2005). In our previous study we showed that the administration of TAM to laying hens resulted in a decrease in the total immunoglobulin concentrations of the blood plasma without alteration of the non-immunoglobular fractions of plasma proteins (Sechman et al, 2004a). In the present study, treatment of laying hens with TAM caused a gradual decrease in egg-laying rate and eventually brought it to an end after twelve days of treatment.…”
Section: (A) (B)mentioning
confidence: 99%
See 1 more Smart Citation
“…We found no difference in posttreatment body mass between tamoxifen-and sham-treated females in this study, and we have evidence that tamoxifen treatment does not adversely affect hematological parameters or endogenous estradiol levels (E. Wagner, unpublished data). In addition, previous studies have found that tamoxifen treatment does not alter body mass, bone density, fat stores, plasma protein and calcium levels, food consumption, or activity level in reproductively mature female birds (Jaccoby et al 1995;Wilson and Thorp 1998;Lupu 2000;Sechman et al 2004). It is also unlikely that tamoxifen had any direct effects on parental behavior and chick provisioning, particularly because treatment did not extend beyond initial stages of egg production and the effects of tamoxifen are transient and reversible (Williams 2000(Williams , 2001.…”
Section: Discussionmentioning
confidence: 97%